2013
DOI: 10.3892/ijmm.2013.1404
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of long non-coding RNAs in bleomycin-induced lung fibrosis

Abstract: Abstract. Recent studies suggest that long non-coding RNAs (lncRNAs) are more involved in human diseases than previously realized. A growing body of evidence links lncRNA mutation and dysregulation to diverse human diseases. However, the association of lncRNAs with the pathogenesis of lung fibrosis remains poorly understood. In this study, we detected changes in hydroxyproline and collagen levels, as well as the ultrastructure of lung tissue to develop a rat model of lung fibrosis. The differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…A recent study by Lv et al identified a large number of lncRNAs that have altered expression in the lungs of rat with experimental fibrosis. This was the first piece of evidence suggesting the participation of lncRNAs in the pathogenesis of pulmonary fibrosis [48]. Among these lncRNAs, several have been previously studied in different biological settings, such as H19, RNA component of mitochondrial RNA processing endoribonuclease (RMRP), and telomerase RNA component (TERC) [103106].…”
Section: Lncrnas In Pulmonary Fibrosismentioning
confidence: 99%
“…A recent study by Lv et al identified a large number of lncRNAs that have altered expression in the lungs of rat with experimental fibrosis. This was the first piece of evidence suggesting the participation of lncRNAs in the pathogenesis of pulmonary fibrosis [48]. Among these lncRNAs, several have been previously studied in different biological settings, such as H19, RNA component of mitochondrial RNA processing endoribonuclease (RMRP), and telomerase RNA component (TERC) [103106].…”
Section: Lncrnas In Pulmonary Fibrosismentioning
confidence: 99%
“…They have been shown to exert comprehensive effects on biological processes through a variety of mechanisms (Mercer et al, 2009;Hu et al, 2012) and are thought to play important roles in the pathophysiology of several diseases, including cancer, pulmonary fibrosis and cardiovascular disease (Cao et al, 2013;Yang et al, 2013;Liu et al, 2014). Moreover, in recent studies, lncRNAs have been discovered that can act as competitive endogenous RNAs (ceRNA) of miRNAs by sharing common miRNA response elements (MREs), inhibiting miRNA activity and attenuating the repression of miRNA-target genes (Ebert and Sharp, 2010;Poliseno et al, 2010;Cesana et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Hyp level in the hydrolysates was colorimetrically determined by absorbance at 560 nm with p-dimethylaminobenzaldehyde and expressed as mg/g wet tissue. 23 Immunofluorescence Rabbit anti-rat a-SMA and anti-E-cadherin antibodies were purchased from Boster Bio-engineering (Wuhan city, China). Immunofluorescence staining was performed as previously described.…”
Section: Transmission Electron Microscopy (Tem) Observationmentioning
confidence: 99%